Literasi Edukasi Aplikasi Keuangan Digital Bukuwarung pada UMKM Warmindo Fortuna dan Warmindo Wisesa - Lussy, Michi; Airawaty, Diana (Sahabat Publikasi, 2024)
Micro, small and medium enterprises (MSMEs) continue to increase because they are the ones that play a greater role in the national economy. There are still many obstacles experienced by MSME actors related to financial management skills which is one of the problems faced. The importance of financial literacy through bookkeeping applications for MSMEs can help MSME actors record financial transactions and make it easier to arrange product sales. This study aims to provide education on the digitization of financial bookkeeping and financial literacy to MSME players Warmindo Fortuna and Warmindo Wisesa with the target that these MSMEs can carry out simple financial bookkeeping. This research was conducted in Depok District, Sleman Regency using qualitative methods. The author collected research data by observation, interviews and documentation. The results of the research show an increase in understanding and knowledge of business actors, it is hoped that this literacy can be felt by MSME business actors.